Coleçao Gilberto Chateaubriand anos 60-70. - Amato, Mario; Chateaubriand, Gilberto; Nascimento Brito, M.F. do; Roels Jr., Reynaldo; de Almeida Amorim, Carlos Cardoso; de Lontra Costa, Marcus (Sao Paulo : SESI (Serviço Social da Industria) - Departamento Regional de São Paulo, 1992)
De Aquino, Adriano ; Maiolino, Anna Maria ; Dias, Antonio ; Henrique Amaral, Antonio ; de Oliveira, Antonio Manuel ; Barrio, Artur Alipio ; Vergara, Carlos ; Zilio, Carlos ; Meireles, Cildo ; Tozzi, Claudio ; Ramosa, Edival ; Sued, Eduardo ; de Andrade, Farnese ; Henrique, Gastao Manuel ; de Morais, Glauco Pinto ; Rodrigues, Glauco ; de Freitas, Iole ; Granato, Ivald ; Machado, Ivens ; Filho, Joao Camara ; Aguillar, José Roberto ; Correia, Luis Gregorio ; de Guimaraens, Luiz Alphonsus ; Machado, Milton ; Leirner, Nelson ; Dillon, Osmar ; Leal, Paulo Roberto ; Collares, Raimundo ; Magalhaes, Roberto ; Macedo, Ronaldo de Rego ; Gerchman, Rubens ; Simoes, Thereza ; Tunga ; Caldas, Waltercio ; Pimentel, Wanda ; Lee, Wesley Duke
Portugees
Coleçao Gilberto Chateaubriand - Anos 60-70, Galeria de arte SESI, Sao Paulo, Setembro 92 - Janeiro 93
boek